Liposomal bupivacaine reduces narcotic use and time to flatus in a retrospective cohort of patients who underwent laparotomy. (November 2018) - Burnett, Atuhani; Faley, Brian; Nyirenda, Themba; Bamboat, Zubin M.
Abstract: Introduction: Sustained release liposomal bupivacaine (LB) is a new pain control option that can reduce opioid use after laparotomy, which is known to prolong ileus, length of stay. Methods: Sixty-one consecutive patients undergoing laparotomy were treated with a standardized multi-modal therapy (MMT) consisting of IV tylenol, toradol, and morphine/dilaudid PCA. Thirty-one of those patients were additionally treated with LB infiltrated during fascial closure. Endpoints were opioid use, time to flatus, length of stay, and complications. Results: Overall opioid use for 72 h was 78 mg of morphine for the MMT + LB group and 112 mg in the MMT control group (p = 0.04). During 0–24 h s PCA use was similar. However, during 24–48 h PCA use was decreased by 46% in the MMT + LB group (p = 0.038), and decreased by 55% during the 48–72 h period (p = 0.019). Time to flatus was decreased by 1.0 days in the MMT + LB group (p = 0.005). Conclusion: Use of LB in laparotomy patients decreases opioid use, time to flatus, and should be considered as a component of post-operative pain control. Highlights: Narcotic use was reduced 30% during the first 72 h post-op in patients who underwent injection of liposomal bupivacaine. Time to flatus was decreased by 1 day in patients who underwent injection of liposomal bupivacaine. Post-operative pain scores were equivalent between both groups. No difference in wound infections or opioid related adverse events were noted between groups.